Further University of Wisconsin materials : further documents of F. Taylor Ostrander - Samuels, Warren J., 1933-; Ostrander, F. Taylor (Research in the history of economic thought and methodology, 2005)
Presents lecture notes from courses at the University of Wisconsin during 1955-6 given by Hans Hl. Gerth and Edwin E. Witte, together with correspondence of Selig Perlman. This volume also presents notes given by John U Nef, Charles O Hardy, and Chester W Wright, on European economic history, money and banking, and U.S. economic history.